Antibacterial effect and mechanisms of action of 460–470 nm light-emitting diode against Listeria monocytogenes and Pseudomonas fluorescens on the surface of packaged sliced cheese. (April 2020) - Hyun, Jeong-Eun; Lee, Sun-Young
Abstract: The aim of this study was to investigate the antibacterial effect of 460–470 nm light-emitting diode (LED460–470nm ) illumination against pathogens and spoilage bacteria on the surface of agar media and packaged sliced cheese. LED460–470nm illumination highly inhibited the growth of Listeria monocytogenes and Pseudomonas fluorescens on agar media covered with oriented polypropylene (OPP) film (thickness, 0.03 mm). When sliced cheeses inoculated with L. monocytogenes or P. fluorescens and packaged with OPP film were illuminated by an LED460–470 nm at 4 or 25 °C, reduction levels of L. monocytogenes and P. fluorescens on packaged slice cheese were higher at 4 °C than at 25 °C. There were no significant differences in color between non-illuminated and illuminated sliced cheese after storage for 7 d at 4 °C. LED460–470 nm illumination at 4 °C for 4 d caused cellular injury of L. monocytogenes and P. fluorescens related to RNA, protein, and peptidoglycan metabolism, and a disruption of the cell membrane and loss of cytoplasmic components were observed from TEM results. These results suggest that LED460–470 nm illumination, in combination with refrigeration temperatures, may be applied to extend the shelf-life of packaged slice cheese and minimize the risk of foodborne disease, without causing color deterioration. Highlights: LED460–470nm could be used to inhibit pathogens on packaged sliced cheese. Bacterial growth inhibition by LED460–470nm was more effective at 4 °C than 25 °C. LED460–470nm inactivated bacteria through the disruption of cell membrane. The antibacterial activity of LED460–470nm was different depending on packaging films.